Barriers in Career Planning for Students in Poland and Italy - Czarnecka, Agnieszka; Miętkiewicz, Monika; Ziemkiewicz-Gawlik, Ilona; Pietrek, Grzegorz Wojciech (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
In the face of dynamic changes in the labour market, this study analyzes the barriers to career planning among students in Poland and Italy. It serves as a crucial tool for understanding the challenges faced by young people. A diagnostic survey was conducted among management students at the WSB Merito University in Poland, and Università degli Studi del Sannio-Benevento in Italy to identify the main difficulties and barriers to career planning. The research sample was selected purposively, focusing on management students as a representative groupof young individuals facing career planning challenges, in accordance with best practices in social science research. The results indicate regional differences: in Poland, issues related to the requirement for full availability and transportation difficulties are predominant, while in Italy, low wages and employment instability are more prevalent problems young people face. Students in both countries actively seek to gain practical experience through work and participation in various training programs. The study highlights the need to focus on developing effective support strategies for students, addressing these differences and better aligning education with labour market demands and contributes to the development of a career management model that supports young people in transitioning from the education system to the labour market. The research findings represent an attempt to create a career management model that supports young people in transitioning from the education system to the labour market.